Exploration of The Meaning of Animal Figures in The Illumination of The Jayalengkara Wulang Jav 24 Manuscript - Dwiadmojo, Ghis Nggar; Mulyani, Hesti; Ekowati, Venny Indria; Hartanto, Doni Dwi (Transpublika Publisher, 2024)
This research aims to investigate the significance of the interpretation of the animal element in the manuscript Jav 24, which contains the text Jayalengkara Wulang, and its relevance to the main doctrine of Javanese leadership, namely Asta Brata. This investigation involves qualitative research using the hermeneutic phenomenological approach of Paul Ricouer. This study limits the interpretation to the illumination elements depicting three animals, namely elephants, lions and crocodiles. As an illuminating element in the text, the elephant represents strength, the lion represents protection from disturbances from the land, and the crocodile represents protection from disturbances from the water. In other words, the animal images as enlightenment elements in this text represent strength and protection. Strength and protection are two of the eight most important Javanese leadership teachings summarized in Asta Brata. Illumination is another manifestation of text so that there is a message contained in this illumination. In order for the message manifested in this illumination to reach the reader, it is necessary to present these illuminations in a more popular form.